2015
DOI: 10.1111/1756-185x.12605
|View full text |Cite
|
Sign up to set email alerts
|

Association ofHLA‐B*27 with ankylosing spondylitis in Kurdish patients

Abstract: From this study, we can conclude that the prevalence of HLA-B*27 among the Kurdish healthy population is 3.8% and there is a strong association between HLA-B*27 and ankylosing spondylitis patients in the Kurdistan Region of Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Among the extra-articular manifestations, anterior uveitis was the most commonly reported, with a rate of 7.1% in this study, which was similar to that reported among Moroccans (6.8%) [9] and Saudis (7%) [14] but lower than that reported in Jordanians (13%) [16], Kurdish (12.2%) [30], Iranians (44.9%) [23] and those living in Qatar (14.5%) [15].…”
Section: Discussionsupporting
confidence: 85%
“…Among the extra-articular manifestations, anterior uveitis was the most commonly reported, with a rate of 7.1% in this study, which was similar to that reported among Moroccans (6.8%) [9] and Saudis (7%) [14] but lower than that reported in Jordanians (13%) [16], Kurdish (12.2%) [30], Iranians (44.9%) [23] and those living in Qatar (14.5%) [15].…”
Section: Discussionsupporting
confidence: 85%
“…(1) assessed the association between K. pneumoniae infection and AS; (2) cohort studies or case-control studies; (3) the K. pneumoniae infections were defined as positive by antibody tests, DNA tests, and isolation and cultivation of bacteria; (4) reporting of corresponding effect estimates (eg, relative risk or odds ratio [OR]) or sufficient data to use in calculations; (5) published in English or Chinese. When there were multiple publications from the same population during an overlapping time period, data from the most recent or comprehensive study were used.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…2 Genetic factors are thought to be related to AS. [3][4][5][6][7][8] It has been reported that more than 90% of AS patients carry the human leukocyte antigen (HLA)-B27 gene. 9Enterobacteria infection, 10 such as with Klebsiella pneumoniae, Proteus mirabilis, Escherichia coli, was deemed in previous studies to be another risk factor causing AS.Among Enterobacteria, K. pneumoniae has received the most attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of samples in the Kurdistan region of Iraq showed that the ratio of males to females was 5.8:1 (7). It was also reported that the peak age range for onset is 15-35 years (5).…”
Section: Introductionmentioning
confidence: 99%